Quantifying the parallel mediation influence of body mass index and depression on physical activity and cognitive function among 3,611 Chinese older adults - Liu, Ji; Qiang, Faying; Dang, Jingxia; Chen, Qiao Yi (Frontiers in Aging Neuroscience, 2022)
Background: Engagement in physically active lifestyles brings multidimensional health benefits including better cognitive function. While prior studies examined the link between physical activity and cognitive function, a remaining unanswered question is what modifiable factors channel such effects. Objective: This study investigates the extent to which subject’s body mass index (BMI) and depression mediate the link between physical activity and cognitive function among older adults in China. Methods: This study builds a parallel structural equation model utilizing the 2013–2018 China Health and Retirement Longitudinal Study (CHARLS) dataset. We screened a total of 14,724 subjects, among which 3,611 subjects met the inclusion criteria. Physical activity, depression, and cognitive function are measured using the International Physical Activity Questionnaire (IPAQ), Center for Epidemiological Research Depression Scale (CES-D), and Mini-Mental State Examination (MMSE) instruments. Results: Parallel mediation analyses indicate that depression significantly mediates the link between physical activity and cognitive function (std. β = 0.023, p-value = 0.010), while no significant mediation was observed via BMI (std. β = 0.005, p-value = 0.155). Findings also show that physical activity is positively associated with cognitive function (std. β = 0.104, p-value = 0.004), whereas physical activity is inversely associated with BMI (std. β = −0.072, p-value = 0.045). Both BMI (std. β = −0.071, p-value = 0.042) and depression (std. β = −0.199, p-value = 0.001) are negatively associated with cognitive function. Conclusion: This study quantifies the positive association between physical activity and cognitive function in older Chinese adults, and uncovers a significant mediation channel occurring through depression. From a clinical perspective, physical behavioral modifications can lead to linked improvements in both mental and cognitive wellbeing.